Expression of HSP in dental root pulp cells due to experimental orthodontic mechanical stress - Nakano, K.; Muraoka, R.; Tomida, M.; Matsuura, S.; Okafuji, N.; Siar, C.H.; Kawakami, T. (2009)
Using immunohistochemical techniques, we examined the expression of heat shock protein (HSP) appearing in murine dental pulp cells after the application of experimental orthodontic mechanical stress We used Waldo's method, and the results demonstrate that the dental root pulp cells expressed HSP in a comparatively short time after stress The results suggest that FISP works as one of the mechanisms to maintain homeostasis